Synthesis and Antimicrobial Activity of 3-Arylimino-4-(4’-benzylidene amino phenyl)-5-phenylimino-1,2,4-dithiazolidenes - V. GANDHE, SHITAL; BERAD, B.N. (Asian Journal of Chemistry, 2010)
A series of 3-arylimino-4-( 4'-benzylidene amino phenyl)-5-phenylimino-1,2,4-dithiazolidenes (5a-f) have been obtained by the basification of their hydrochlorides (4a-f), which were synthesized by the interaction of N-phenyl-S-chloro-isothiocarbamoyl chloride and 1-(4'-benzylidene amino phenyl)-3-aryl thiocarbamides (3a-f). The latter were synthesized by the condensation of benzaldehyde and different 1-(4' -amino phenyl)-3-aryl thiocarbamides (2a-f). (2a-f) were synthesized by refluxing p-phenylene diamine and different aryl isothiocyanates (1a-f) in CHCl3 medium. Bromination of (5a-f) by bromine in glacial acetic acid gave dibromoderiyatives. The title compounds were assayed for their antimicrobial activity against gram-positive as well as gram-negative microorganisms.